2018
DOI: 10.14791/btrt.2018.6.e7
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Pituitary Apoplexy after Chemotherapy in a Patient with Metastatic Breast Cancer

Abstract: Surgery, anticoagulation therapy, pregnancy, and hormone treatments, such as bromocriptine, are well-characterized precipitating factors for pituitary apoplexy. However, whether cytotoxic chemotherapy for systemic cancer could cause pituitary apoplexy has not been investigated. Here, we present a case of a 41-year-old woman who developed a severe headache with decreased visual acuity after intravenous cytotoxic chemotherapy to treat metastatic breast cancer. Preoperative neuroimaging revealed pituitary adenoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Given the complex array of side effects that often accompany chemotherapy treatment and the potential for PA to present insidiously rather than acutely [ 17 - 18 ], the incidence of PA in patients in this setting is likely underappreciated. In the absence of formal guidelines, because the risk of chemotherapy-related PA is theoretically increased with macro- versus microadenomas, we agree with previous authors that prophylactic surgical removal may be considered for patients with known or incidentally identified larger pituitary tumors requiring cytotoxic chemotherapies to reduce PA risk [ 5 ]. This decision must nonetheless balance the oncologic risk of delaying chemotherapy.…”
Section: Discussionsupporting
confidence: 83%
“…Given the complex array of side effects that often accompany chemotherapy treatment and the potential for PA to present insidiously rather than acutely [ 17 - 18 ], the incidence of PA in patients in this setting is likely underappreciated. In the absence of formal guidelines, because the risk of chemotherapy-related PA is theoretically increased with macro- versus microadenomas, we agree with previous authors that prophylactic surgical removal may be considered for patients with known or incidentally identified larger pituitary tumors requiring cytotoxic chemotherapies to reduce PA risk [ 5 ]. This decision must nonetheless balance the oncologic risk of delaying chemotherapy.…”
Section: Discussionsupporting
confidence: 83%
“…( Table 1 ) Headache was severe, often described as the most painful headache episode an individual has ever experienced, and graded, for example, as high as 9 on a scale from 0 to 10, with 10 being the most severe in one study [ 31 ]. For practical purposes we point out that headache was absent in some cases; thus, an index of suspicion should be provided by other endocrine and non-endocrine clinical elements [ 43 , 86 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 ]. For instance, Enatsu et al reported a 65-year-old woman admitted for a nonfunctioning pituitary adenoma-associated PA who presented third cranial nerve palsy and sudden decrease in visual acuity unaccompanied by headache [ 196 ].…”
Section: Pitnet Complicated With Pamentioning
confidence: 99%
“…Visual field defects varied from (mostly common) hemianopia [ 33 , 39 , 55 , 80 , 126 , 135 , 179 , 187 , 197 ] to cranial nerve palsies manifesting as diplopia in the majority of these cases [ 32 , 34 , 35 , 49 , 50 , 58 , 63 , 66 , 68 , 75 , 84 , 85 , 91 , 92 , 114 , 115 , 117 , 127 , 130 , 142 , 147 , 150 , 157 , 163 , 164 , 186 , 191 , 194 , 195 , 207 , 214 ] followed by ptosis [ 34 , 35 , 50 , 59 , 75 , 77 , 79 , 92 , 107 , ...…”
Section: Pitnet Complicated With Pamentioning
confidence: 99%
See 2 more Smart Citations